PENGARUH KINERJA KEUANGAN DAN FAKTOR EKONOMI MAKRO DALAM MEMPREDIKSI VOLATILITAS HARGA SAHAM PERUSAHAAN SUBSEKTOR INDUSTRI FOOD AND BEVERAGES - Ilmiyono, Agung Fajar (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2017)
ABSTRACTThis study aims to analyze and test the effect of financial performance and macro economic to stock price volatility in food and beverages companies listed in the Indonesia Stock Exchange period 2012-2016. Thirtyfive samples are tested by classical assumption using multiple regression analysis technique. The result shows that the financial performance partially has no significant effect on stock price volatility and macro economic partially has no significant effect on stock price volatility. Keywords: ROA, DER, Net Cash Flow, Inflation, Exchange Rate, Interest Rate, and Volatility Stock Price